Thermal behavior of nanoparticle enhanced phase change material discharging in existence of complex geometry. (March 2023) - Qahiti, Raed; Almarashi, Adel; Hamali, Waleed
Abstract: Freezing process inside thermal system has been simulated via finite element method to manage the performance of system. The pure material is water which can mix with nanoparticles utilizing various volume and shapes. Grid generation has been done according to technique of grid adaption and discretization of transient terms was done based on implicit approach. With removing momentum equations according to low magnitude of liquid phase and applying single phase approach for NEPCM, the model of freezing has been derived and FEM was selected to solve it. The procedure of simulation has been verified and good accommodation has been reported. For generating ice in whole domain in absence of nano-powders, 608.78 s should be passed. Adding powders with m = 4.8 and 8.6 can reduce the time around 21.36 % and 26.85 %. The liquid NEPCM can converts to solid after 445.27 s if nanoparticles have been applied. Highlights: The freezing process has been simulated via FVM to manage the performance of system. For reaching SF = 1 in absence of nano-powders, 608.78 s should be passed. Adding powders with m = 4.8 and 8.6 can reduce the time around 21.36 % and 26.85 %.